DETERMINATION OF FACTORS OF TERRITORIAL CONNECTION OF THE COUNTRY FOR DEVELOPMENT OF MULTIMODAL AIR TRANSPORT SYSTEM - Tikhonov, Alexey; Sazonov, Andrey (Journal of Applied Engineering Science, 2022)
In modern economic realities, scientific and technical programs and innovative projects of a full cycle should become the dominant tools necessary for the effective implementation of the strategy of scientific and technological development of the Russian Federation. Specially created сouncils, the scope of which is related to the determination of priorities in the development of national science, should carry out the procedures for the formation and expert selection of innovative programs / projects of the full cycle. A list of complex scientific and technological projects proposed in the formation of the list of measures for 2020-2022 within the framework of the subprogram "Aviation Science and Technology" of the State Program of the Russian Federation "Development of Aviation Industry for 2013-2025" was compiled. A list of general goals of scientific and technological development of aircraft construction is presented. The most priority directions of scientific and technological development of modern civil aircraft construction have been determined. The authors considered the main goals, objectives and composition of the components included in the integrated air transport system. As a practical example, the formation of the appearance of a promising air transport system in terms of creating innovative technologies for existing and future aircraft, taking into account its integration into the multimodal transport system of the Russian Federation, is considered. The authors of the article propose a new approach to the development of a program / project of a complete innovation cycle based on the use of "gate" approach. The tasks of interaction with the Ministry of Transport of the Russian Federation on the creation of air transport system are considered.
Keywords: territorial connectivity of the country, strategic development programs, multimodal transport system, comprehensive scientific and technological programs, projects of complete innovation cycle, development of air transport system, development of territories, intelligent transport and logistics systems